2020
DOI: 10.1038/s41598-020-69173-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bacterial lipopolysaccharides on platelet function: inhibition of weak platelet activation

Abstract: Platelets are anucleate blood cells with reported roles in hemostasis and immune responses, which possess a functional receptor for bacterial lipopolysaccharides (LPSs), the well-known inducers of inflammation. However, LPSs effects on platelets are contradictory. Here we aim to investigate mechanisms of platelet functioning in the presence of LPS and to find the cause of the discrepancy in the previously published data. Cell activity was analyzed by flow cytometry, western blotting, and aggregometry. Thrombus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…An endotoxin is a LPS released by most Gram-negative bacteria and is located in the outer membrane of their cell wall [ 17 , 20 , 21 , 22 , 23 ]. The outer layer of the cell wall is composed of an asymmetric phospholipid bilayer that contains the LPS, and the inner layer of the membrane includes glycerophospholipids.…”
Section: Endotoxin As a Component Of Gram-negative Bacteriamentioning
confidence: 99%
“…An endotoxin is a LPS released by most Gram-negative bacteria and is located in the outer membrane of their cell wall [ 17 , 20 , 21 , 22 , 23 ]. The outer layer of the cell wall is composed of an asymmetric phospholipid bilayer that contains the LPS, and the inner layer of the membrane includes glycerophospholipids.…”
Section: Endotoxin As a Component Of Gram-negative Bacteriamentioning
confidence: 99%
“…Due to differences in the experimental protocols, the influence of LPS on platelet activity cannot be clearly defined. However, Martyanov et al showed that LPS restored the response to ADP in desensitized platelets by activating platelet TLR4 while inhibiting platelet activation by potentiating cAMP/cGMP pathways [24]. This could explain why the most pronounced increase in the PECAM-1/thrombus ratio observed in the LPS + ASA 3 mg/kg group (Figures 1b and 2d) was opposite to the tendency observed in control mice (Figure 2b).…”
Section: Mouse Studymentioning
confidence: 84%
“…The last secondary mediator of platelet signaling is the cytosolic concentration of cyclic nucleotides -cAMP and cGMP [51]. Cyclic nucleotides are generated by cyclases: adenylate cyclase (cAMP from ATP) and guanylate cyclase (cGMP from GTP) and are converted into monophosphoribonucleotides by low-specific phosphodiesterases (PDE) [52].…”
Section: Secondary Messengers Of the Plateletsmentioning
confidence: 99%